IT technologies in the digital transformation of separate branches of economy: Semiotic perspective - Danchenko Nadezhda; Litvishko Olga; Volov Murat (E3S Web of Conferences, 2023)
The article is devoted to the study of the influence of IT technologies on modern processes of digitalization of economy, which gives quite an extensive research material for various theoretical studies including economics, finance, sociology, linguistics. It is noted that not all social or communicative phenomena can be explained exclusively with the help of categories of one or another school of thought. The authors propose looking at the impact of IT technologies on economic phenomena through the lens of semiotic analysis to understand the results of implementing advanced IT technologies in such socio-economic process as digitalization. The results of the research show that semiotic analysis not only reveals the range of sign systems used in the representation of digitalization but also serves as an explanatory tool for learning specific characteristics and objective patterns of polycode texts present in digital products such as websites or mobile applications. The authors are convinced that drawing the methodological tools of semiotics to the analysis of the influence of IT technologies on the process of digitalization of retail financial services will significantly contribute to cross-disciplinary studies of such topical phenomenon as IT technologies and their successful implementation in separate branches of economy.